THE EFFECT OF TEACHING STRATEGIES AND LEARNING STYLE ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Fitri, Ayu (Jurnal Sosial Humaniora Sigli, 2020)
The objectives of this experimental research were to investigate whether: 1) students’ achievement in reading comprehension taught by using advance organizer strategy was higher than taught by using reciprocal strategy. 2) students’ achievement in reading comprehension with visual style was higher than that students with verbal style, and 3) there was interaction between teaching strategies and learning styles on students’ achievement in reading comprehension. The population of this research was the students in grade X of private senior high school named SMA Kartika I-1 Medan in 2012/2013 school year. The total number of population was five classes containing 200 students. There were two classes containing 83 students chosen as sample of this research by applying cluster random sampling technique. In further, there was cluster random assignment done in both two classes in order to know the position of the class whether as experimental group 1 or experimental group 2.The experimental group 1 was treated by using advance organizer strategy and the experimental group 2 was treated by using reciprocal strategy. Then,the research design was experimentby using factorial design 2x2 because there is two independent variables (teaching strategies) and two attributives (learning styles). The questionnaire was conducted for classifying the students’ learning style upon the visual and verbal. Next, students’ achievement in reading comprehension text was measured by using reading comprehension test. The data were analyzed by applying two- way analysis of variance (ANOVA) at the level of significance ?= 0,05. The result reveals that (1) students’ achievement in reading comprehension taught by using advance organizer was higher than that taught by using reciprocal strategy, with Fobs= 9,1>Ftab= 3,96, (2) students’ achievement in reading comprehension with visual learning style was higher that that with verbal learning style, with Fobs=11,7 >Ftab= 3,96,(3) there is  interaction between teaching strategies and learning styles on students’ achievement in reading comprehension with Fobs= 47,4>Ftab= 3,96. Moreover, Tuckey-Test result also showed that visual style students got higher achievement if they were taught by using advance organizer strategy while verbal style students got higher achievement if they were taught by using reciprocal strategy.